Pengaruh Literasi Keuangan, Gaya Hidup Hedonis dan Sikap Keuangan Pribadi Terhadap Perilaku Keuangan Pada Generasi Z di Kota Semarang - Chasanah, Sofa Dwi; Setiyono, Taufiq Andre (Jurnal Inovasi Akuntansi (JIA), 2025)
This study aims to examine the effect of financial literacy, hedonistic lifestyle, and personal financial attitudes on the financial behavior of Generation Z in Semarang City. The sample in this study consisted of active Accounting undergraduate students who belong to Generation Z and reside in Semarang City. The sampling technique used was purposive sampling. The type of data used in this study is quantitative, with primary data collected through questionnaires. The data analysis technique employed in this research is multiple linear regression analysis processed using SPSS. The results of the study show that financial literacy has a positive and significant effect on financial behavior, hedonistic lifestyle does not have a negative significant effect on financial behavior, and personal financial attitudes have a positive and significant effect on financial behavior. Simultaneously, all three variables significantly influence the financial behavior of Generation Z in Semarang.